2015
DOI: 10.1073/pnas.1513341112
|View full text |Cite
|
Sign up to set email alerts
|

Roles of unphosphorylated ISGF3 in HCV infection and interferon responsiveness

Abstract: Up-regulation of IFN-stimulated genes (ISGs) is sustained in hepatitis C virus (HCV)-infected livers. Here, we investigated the mechanism of prolonged ISG expression and its role in IFN responsiveness during HCV infection in relation to unphosphorylated IFN-stimulated gene factor 3 (U-ISGF3), recently identified as a tripartite transcription factor formed by high levels of IFN response factor 9 (IRF9), STAT1, and STAT2 without tyrosine phosphorylation of the STATs. The level of U-ISGF3, but not tyrosine phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(127 citation statements)
references
References 37 publications
(63 reference statements)
4
105
1
Order By: Relevance
“…In line with this hypothesis, Sung et al recently demonstrated that expression of unphosphorylated ISG-F3 is increased by endogenous IFN in HCV-infected livers, leading to persistent activation of a set of ISGs and a lack of response to IFN-α in chronic HCV infection [41]. …”
Section: Discussionmentioning
confidence: 99%
“…In line with this hypothesis, Sung et al recently demonstrated that expression of unphosphorylated ISG-F3 is increased by endogenous IFN in HCV-infected livers, leading to persistent activation of a set of ISGs and a lack of response to IFN-α in chronic HCV infection [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the level of expression of several ISGs was shown to correlate with IFN-λ genotypes, with the unfavorable alleles associated with higher hepatic levels of ISGs (37, 38). Unphosphorylated IFN-stimulated gene factor 3 (ISGF3) is induced by type III IFNs and sustains expression of USP18, a negative regulator of IFN signaling, resulting in unresponsiveness to IFN-α treatment (39). Comparison of levels of ISGs before and after treatment further demonstrated that the high basal expression levels in non-responders did not increase above pretreatment level, whereas there was a strong ISGs induction in the SVR group (40).…”
Section: Mechanisms Underlying the Role Of Ifn-λ Polymorphisms In Hcvmentioning
confidence: 99%
“…Many target genes of U-STATs 1, 2, 3, and 6 encode proteins that promote cell survival and resistance to cell death, suggesting that the U-STAT system helps to sustain the survival of cells in stressful environments. U-STAT1 induces its target genes as U-ISGF3, a tripartite complex with U-STAT2 and IRF9, and the expression of all three U-ISGF3 components is increased in response to either type I or type III IFN Sung et al 2015). U-STAT1 does not activate gene expression as a homodimer, because high levels of U-STAT1 do not induce target gene expression if U-STAT2 and IRF9 are not present in sufficient quantities (Cheon and Stark 2009;Cheon et al 2013).…”
Section: U-stats As Positive Regulators Of Gene Expressionmentioning
confidence: 99%
“…Cancer cells that express high levels of U-ISGF3 are more resistant to DNA damage, while IFNs inhibit cancer cell proliferation and increase their apoptosis (Borden et al 2007). Similarly, hepatocytes expressing high levels of U-ISGF3 are more resistant to IFN-a therapy, although U-ISGF3 itself suppresses viral replication by inducing antiviral genes (Sung et al 2015). Phosphorylated STAT3 mediates the induction of U-STAT3 in response to IL-6 and other cytokines that activate gp130-linked receptors (Yang et al 2005).…”
Section: U-stats As Positive Regulators Of Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation